Kinetics of isothermal and non-isothermal crystallization of poly(vinylidene fluoride) by fast scanning calorimetry. (15th January 2016) - Gradys, A.; Sajkiewicz, P.; Zhuravlev, E.; Schick, C.
Abstract: Crystallization from melt of poly(vinylidene fluoride) was studied by thin film chip calorimetry at cooling rates from 500 to 100, 000 Ks −1 and isothermally down to 76 °C. At ca. 70 °C, for cooling rates higher than 2000 Ks −1, there appears a change in crystallization from high temperature α phase to low temperature β phase. The amorphous state is preserved at cooling rate 100, 000 Ks −1 . Analysis of the crystallization kinetics with Ziabicki model reveals maximum of the steady-state crystallization rate of β phase as 2200 s −1 at 22 °C, and the highest crystallization rate of α phase as 200 s −1 at 70 °C. Approximation of the temperature dependent steady-state crystallization rate with the Turnbull and Fisher nucleation model results in the equilibrium melting temperatures 227 and 173 °C for the α and β phase, respectively, and in the energy barrier for short-distance transport, E D, as 70–80 kJ mol −1 at high supercooling. Graphical abstract: Highlights: Melt crystallization at ultra-high cooling rates using thin-film chip calorimetry. Steady-state crystallization rate of the α and β phase obtained with Ziabicki model. Approximation of the rate with the Turnbull and Fisher nucleation theory. Equilibrium melting temperatures and the energy barrier for short-distance transport.